P-68 Do not attempt cardiopulmonary resuscitation (DNACPR) audit: DNACPR completion and advance care planning at a cancer hospital in sheffield teaching hospitals (STH). (20th March 2022) - Sharrack, Sana; Pitsillides, Constantina; Lawrence, Esther; Smith, Eleanor M
Abstract : Background: 'Addressing decisions surrounding Cardiopulmonary Resuscitation (CPR) is important for any patient who is approaching end of life and/or is at risk of cardiorespiratory arrest' (Resuscitation Council, 2016). Our audit aimed to establish if current practice of DNACPR form completion and documentation was in keeping with local guidelines and if unwell patients had appropriate escalation plans documented. Methods: DNACPR forms for inpatients were reviewed retrospectively (n=35). Data was collected by doctors who were not directly involved in completion of the forms. In addition, medical notes for newly admitted patients who were identified as having a National Early Warning Score (NEWS) of >5 and >7 were reviewed to identify if an escalation plan had been put in place on the post take Consultant ward round (n = 20). Results: 100% of completed DNACPR forms had correct patient identifiers and the reason for DNACPR completion clearly documented. However only 80% were countersigned by the Consultant in the required time (by the end of the next normal working day). Documentation in patient notes was completed for 97% of DNACPR discussions and 86% of DNACPR decisions were documented on the ward handover sheet. Only 57% had time for review clearly stated (unlimited or specific date specified). For patients who were identified as having a NEWS of 5–6, 60% had an appropriate escalation plan documented in the notes, compared to only 40% for those with a NEWS of 7 or above. Conclusion: Our audit identified shortcomings in meeting some of our standards and in making escalation decisions for patients with high NEWS. Staff education in DNACPR completion and facilitating interdisciplinary communication regarding such decisions in a timely manner are essential to ensuring dignified end of life care.